SKYHOOK CHURCHILL 1964 - Fendrich, G W (1964)
A series of high altitude SKYHOOK balloon flights from Ft. Churchill, Manitoba, Canada is discussed. The task called for furnishing personnel and facilities necessary to conduct flights during the period of mid-June to mid August and included: (1) Fabrication and supply of balloons and balloon safety, destruct, and flight control instrumentation. (2) Performance of necessary launching, aircraft tracking and recovery operations for each flight. (3) establishment and maintenance of close liaison with the scientific investigators, base officials, and Canadian authorities. (4) Provision of advice and assistance, as necessary, to the scientific experimenters responsible for the payloads. The background of the selection of Ft. Churchill as launch site and a description of present facilities are covered in the Introduction. (Section I). A description of the program, including launch procedures, tracking and recovery techniques, and a description of the flight control instrumentation are covered. An analysis of the 1964 program is presented along with flight data. A total of 32 balloons were inflated during the period of 16 June 1964 to 17 August 1964. See also AD421823.